2021
DOI: 10.1111/papt.12358
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, compassion, and theory of mind in obsessive‐compulsive disorder

Abstract: Objectives. Individuals with obsessive-compulsive disorder (OCD) often suffer from impairments in social functioning. This study investigates differences in empathy, compassion, and Theory of Mind (ToM) in individuals with OCD as a possible cause for social functioning deficits.Design. Sixty-four individuals diagnosed with OCD and 62 healthy individuals completed a naturalistic behavioural task (EmpaToM) and a self-report measure (Interpersonal Reactivity Index, IRI). Methods. Three preregistered repeated meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The lack of differences for the other facets of social affect and cognition might be a result of every disorder having its own specific social affect and cognition pattern. For example, aggressive offenders exhibit higher cognitive empathy and lower affective empathy (Winter et al, 2017), whereas people with depression or obsessive-compulsive disorder exhibit higher affective empathy (O’Connor et al, 2002; Salazar Kämpf et al, 2022) compared with nonclinical samples. Another suggestion by McRae and Gross (2020) is that people with mental disorders might use adaptive emotion regulation successfully when cued in the laboratory; however, they do not use it frequently in their everyday lives, which is in line with the idea that they might have difficulties fitting a strategy to a situation (Haines et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of differences for the other facets of social affect and cognition might be a result of every disorder having its own specific social affect and cognition pattern. For example, aggressive offenders exhibit higher cognitive empathy and lower affective empathy (Winter et al, 2017), whereas people with depression or obsessive-compulsive disorder exhibit higher affective empathy (O’Connor et al, 2002; Salazar Kämpf et al, 2022) compared with nonclinical samples. Another suggestion by McRae and Gross (2020) is that people with mental disorders might use adaptive emotion regulation successfully when cued in the laboratory; however, they do not use it frequently in their everyday lives, which is in line with the idea that they might have difficulties fitting a strategy to a situation (Haines et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using the Coping Orientations to the Problems Experienced (COPE) Inventory (Carver, 1997) indicate that avoidant thought and action tendencies are associated with depression, anxiety, and stress (Mahmoud et al, 2012) as well as limited physical functioning in people with medical conditions (Eisenberg et al, 2012). Moreover, differences in social affect and cognition have been found in clinical samples, resulting in typical social affect and cognition patterns: For instance, impaired cognitive empathy has been identified as a key symptom in patients with eating disorders (Mansour et al, 2016), impaired (affective) empathy has been associated with obsessive-compulsive disorder ( Jansen et al, 2020;Salazar Kämpf et al, 2022) and schizophrenia (Bonfils et al, 2017;Green et al, 2015). Schreiter et al (2013) reported a positive association between empathic distress (i.e., shared pain) and depressive symptoms.…”
Section: Clinical Samples Versus Nonclinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This discrepancy between self-reported and experimental measures of ToM has also been presented by other studies. 32 For instance, studies have shown very small positive correlations between the IRI and ToM experimental approaches [32][33][34] or differences between groups restricted to one dimension of the cognitive empathy subscale of the IRI and experimental ToM measures. 33,34 This is in line with results of a recent meta-analysis indicating that self-report scores for cognitive empathy account for approximately 1% of the variance in behavioral cognitive empathy assessment.…”
Section: Discussionmentioning
confidence: 99%
“…32 For instance, studies have shown very small positive correlations between the IRI and ToM experimental approaches [32][33][34] or differences between groups restricted to one dimension of the cognitive empathy subscale of the IRI and experimental ToM measures. 33,34 This is in line with results of a recent meta-analysis indicating that self-report scores for cognitive empathy account for approximately 1% of the variance in behavioral cognitive empathy assessment. 35 The findings in this systematic review point to an increased ability of ToM in the peripartum period that is only detected by means of experimental ToM tasks but is not perceived by parents themselves when assessed with selfreport measures.…”
Section: Discussionmentioning
confidence: 99%